Influence of Styrene-Butadiene-Styrene Polymer on Local Asphalt Characteristics - Aso Faiz Talabany; Wlat Dlshad ahmed; Balen Marwan abdulahad; Muhammad sabr sulaiman (Zanco Journal of Pure and Applied Sciences, 2022)
In this study the effect of Styrene-Butadiene-Styrene (SBS) polymer on local asphalts was investigated by comparing the performance of unmodified asphalt binder and hot mixture with binder and mixtures modified by SBS polymer modified asphalt (SBS-PMA) and its hot mixture. The comparison was made by evaluating the effectiveness of using different percentages (dosages) of this modifier to produce SBS-PMA. The penetration, ductility, elastic recovery, softening point, flash point, penetration and loss on heat tests for the asphalt binder was used. While, Marshall, indirect tensile strength (ITS), and index of retained strength (IRS) tests for the mixture was used in this study as they are the most available and economic. SBS polymer modifier was added to asphalt binders from Kirkuk governorate (KAT) and LANAZ refineries in Erbil governorate-Kurdistan region- Iraq in four percentages 3%, 5%, 7% and 9% by weight of the asphalt binder. The results showed that SBS polymer modifier significantly enhances the performance of asphalt binder and its hot mixture resulting in enhanced flexible pavements. However, adding 5% SBS leads to the best results of the Marshall test properties, and the moisture damage resistance, which increases the pavement performance against the environmental effects. Comparing the experimental results for both unmodified and 5% SBS polymer modified asphalts, showed that the replacement of the unmodified asphalt by 5% SBS polymer modified asphalt increased the stability by 26.00% for KAT asphalt and 21.34 % for LANAZ asphalt. Also, it increased the TSR by 15.63 % for KAT asphalt and 7.95 % for LANAZ asphalt and the IRS by 11.92% for KAT asphalt and 7.11 % for LANAZ asphalt. The regression analysis technique was applied to fit the mathematical relationship between the SBS polymer percentage and the Marshall stability of the hot mixture. Based on this investigation, the polymer modified asphalt is recommended to be used in new constructed roads to help reduce the amount of deterioration and maintenance cost in the region.